As múltiplas dimensões da participação grupal: um estudo de caso sobre um clube de mães da Zona Sul de São Paulo - Oliveira, José Hercilio Pessoa de (2015)
We aim to understand how multiple dimensions of group participation enabled a Mothers Club to remain in time. Our research tries to recognize learning and sharing skills through exchange practices in that group. We also attempt to the affection involved and how it nurture relationships within and outside the group. We highlight the ways by which assemblages and debates within the group may extend spaces for participants to claim for their rights and foster their commitment and influence in actions developed by the State. We assume a constructionist perspective, which leads us to focus on the specific ways by which the group organize conversation and make it easier between participants. We moved our focus from group as a phenomenon to group practices and we propose an understanding of group as a social construction. The group we focused as case study is Lady Mila s Mothers Club, created in the 1969. We engaged in conversations within the group in order to understand how participants worked together in the group and also to recover the group timeline, which gave us visibility to the diversity of historical moments shared by the participants. We also performed four individual interviews in order to give visibility to discursive positioning and dialogues in speeches which were analysed using dialogic maps. The maps we produced made it possible to identify two major themes related to the group history: the operational characteristics of the group and the support of the group during regular activities. We conclude that the possibility of sharing emotions and abilities, the coexistence of activities within and outside the group, the exchange of knowledge and the ability to generate income, contributed to the group permanence over the past 45 years